Low-temperature CO catalytic oxidation catalyst with high sulfur resistance as well as preparation method and application of low-temperature CO catalytic oxidation catalyst

By loading Pd and additive metal on TiLaAlOx composite metal oxide support, a low-temperature CO catalytic oxidation catalyst with high sulfur resistance is prepared, which solves the problem of catalyst in the prior art in high temperature or sulfur-containing atmosphere, and realizes the problem of inactivation of the catalyst in the high temperature or sulfur-containing atmosphere. High-efficiency catalytic combustion of CO under low temperature conditions is suitable for the steel industry.

CN119281325AActive Publication Date: 2025-01-10ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411585665.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-10
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing CO catalysts are prone to deactivate in high temperature or sulfur-containing atmospheres, and cannot meet the needs of high sulfur resistance in the steel industry, especially under low temperature conditions.

Method used

TiLaAlOx composite metal oxide is used as a carrier to load precious metal Pd and additive metals Co, Cr, Cu, Sn, Mo, W, Fe, Y, Ni, Nb. High sulfur resistance is prepared by loading Pd by equal volume impregnation method. low temperature CO catalytic oxidation catalyst.

Benefits of technology

The catalyst maintains high activity in an environment of 300ppm SO2, has stable conversion rate of CO gas, and is suitable for catalytic combustion of steel exhaust gas. It has low cost and simple process and has great industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281325A_ABST
    Figure CN119281325A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature CO catalytic oxidation catalyst with high sulfur resistance and a preparation method and application thereof. A carrier of the catalyst is a TiLaAlOx composite metal oxide, an active component and an auxiliary metal M are loaded on the carrier, the active component is precious metal Pd, the auxiliary metal M is one or more of Co, Cr, Cu, Sn, Mo, W, Fe, Y, Ni and Nb, the loading amount of Pd is 0.1-4%, and the loading amount of the auxiliary metal M is 0.5-5%; the molar ratio of Ti to La to Al in the TiLaAlOx composite metal oxide is (5-15): (5-15): 80. The prepared catalyst is especially suitable for catalytic combustion of steel tail gas CO, has high sulfur resistance, can still keep high activity to CO gas in a 300 ppm SO2 environment, and has great industrial application potential and value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of air pollution control, and in particular to a low-temperature CO catalytic oxidation catalyst with high sulfur resistance, a preparation method thereof, and an application thereof. Background Art

[0002] The catalytic oxidation method completely burns toxic CO and converts it into CO2. It has the advantages of high purification efficiency, no secondary pollution, low energy consumption, and large heat release. It is considered to be the most effective means of eliminating CO. However, the catalyst is easily poisoned and deactivated in a high temperature environment or in a sulfur- or chlorine-containing atmosphere. The CO concentration in steel sintering flue gas is high, and the heat released by catalytic combustion can just increase the flue gas temperature, thereby ensuring the temperature required for the back-end SCR denitrification reaction. Therefore, the development of highly stable catalysts is a key technology for steel sintering gas treatment. However, steel sintering gas contains a certain concentration of SO2, and the CO catalyst is easily deactivated in a sulfur-containing atmosphere. When the volume fraction of sulfide exceeds 5×10 -6 , the activity of the catalyst will be inhibited. Sulfur-containing compounds will compete with reactants for adsorption active sites during the catalytic reaction, which may cause a temporary decrease in activity, or even react with the main active species or carrier to form sulfites or sulfates, causing irreversible chemical deactivation.

[0003] At present, many patents on catalysts for CO oxidation elimination have been reported at home and abroad, such as CN109092304A, which discloses a Pt-based catalyst prepared by combining microwave heating and atomic capture, which can eliminate CO at medium and low temperatures, but the anti-sulfur performance is not described, and the preparation process is cumbersome and the energy consumption is large. CN116060036A discloses an integral catalyst prepared by co-loading copper, manganese and platinum-based elements. Although it has certain sulfur resistance, it can only maintain good stability at a high temperature of 500°C, which is not suitable for the application scenario of steel sintering gas and is not suitable for large-scale industrial use. CN118142520A discloses a core-shell catalyst with nano Pt, Pd, and Ru nanoparticles, an outer shell of SnO2, and a carrier containing Sn metal oxide. In the CO oxidation process containing 10ppm SO2, the catalyst shows high catalytic activity and stability, which does not meet the scenario of large-scale industrial application. The existing CO catalysts have a very low activation temperature, but the sulfur resistance performance needs to be improved. The activation temperature required for actual engineering applications is not very low, especially in the steel industry, where the flue gas temperature is mostly above 160°C. Engineering applications have very high requirements for the sulfur resistance of catalysts, which is also the key to whether the catalyst can be used. Therefore, the preparation of an efficient, sulfur-resistant and stable low-temperature CO catalytic oxidant is of great significance to the green development of the steel industry. Summary of the invention

[0004] In order to solve the above technical problems existing in the prior art, the object of the present invention is to provide a low-temperature CO catalytic oxidation catalyst with high sulfur resistance and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The low-temperature CO catalytic oxidation catalyst with high sulfur resistance is a catalyst with a carrier of TiLaAlO x The composite metal oxide is loaded with active ingredients and auxiliary metal M on the carrier, the active ingredient is precious metal Pd, the auxiliary metal M is one or more of Co, Cr, Cu, Sn, Mo, W, Fe, Y, Ni, Nb, the Pd loading is 0.1-4%, and the auxiliary metal M loading is 0.5-5%; the TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is 5-15:5-15:80.

[0007] Furthermore, the Pd loading in the catalyst is 0.5-2%, the auxiliary metal M loading is 1-2%, and the TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is 8-12:8-12:80.

[0008] Furthermore, the auxiliary metal M is one or both of Ni and Y.

[0009] The method for preparing a low-temperature CO catalytic oxidation catalyst with high sulfur resistance comprises the following steps:

[0010] S1: According to TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is adjusted, La(NO3)3·6H2O and Al(NO3)3·9H2O are dissolved in water, a titanium isopropoxide solution diluted with an ethanol solvent is added dropwise thereto, a base is added to adjust the pH to 8.0-10.0, and the mixture is stirred for 0.5-4h; then, it is aged at room temperature for 10-15h, filtered, washed with deionized water and anhydrous ethanol for multiple times until the filtrate is neutral, dried, and calcined at 300-600°C in an air atmosphere for 2-5h to obtain TiLaAlO x Composite oxide powder;

[0011] S2: Dissolve the nitrate of metal M in deionized water and add TiLaAlO x The composite oxide powder is stirred in a water bath at 50-70°C for 20-60 minutes, the obtained mixture is subjected to vacuum rotary evaporation to remove excess water to obtain a solid powder, which is dried overnight and calcined at 300-600°C for 2-5 hours to obtain a modified carrier TiLaAlOx-M;

[0012] S3: The precious metal is loaded by the equal volume impregnation method. The carrier powder obtained in step S2 is impregnated in the Pd precursor aqueous solution. The obtained mixture is stirred in a water bath at 65-85°C for 1-3 hours to allow the precious metal Pd to be fully adsorbed on the carrier surface. The mixture is then filtered, dried, and calcined at 300-600°C in an air atmosphere for 2-5 hours. The preparation is completed.

[0013] Furthermore, in step S1, S2 or S3, the calcination temperature is 380-420°C.

[0014] Furthermore, in step S3, the temperature of the stirring reduction reaction is 65-85° C., and the reaction time is 0.5-2 h.

[0015] The application of the low-temperature CO catalytic oxidation catalyst with high sulfur resistance in catalytic combustion of CO is that the catalyst is loaded in a tubular reactor, heated to the reaction temperature of catalytic combustion, and the CO gas is diluted with air as a diluent to form a gas raw material, which is introduced into the tubular reactor for catalytic combustion reaction.

[0016] Furthermore, the CO gas concentration in the gas raw material is 1000ppm to 20000ppm, preferably

[0017] 5000-10000ppm, SO2 gas concentration in gas raw material is 0-600ppm, reaction space velocity is 20000-80000mL·g -1 ·h -1 The reaction temperature of the catalytic combustion is 160-250°C, preferably 200-220°C.

[0018] Furthermore, the SO2 gas concentration in the gas raw material is below 300 ppm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts chloropalladium (PdCl4), titanium isopropoxide Ti(OCH(CH3)2)4, lanthanum nitrate hexahydrate La(NO3)3·6H2O, and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) as main raw materials, and adopts an equal volume impregnation method to load Pd to prepare Pd / TiLaAlO x-M catalyst (M is one or more of Co, Cr, Cu, Sn, Mo, W, Fe, Y, Ni, Nb, etc.), the Pd loading in the catalyst is 0.1-4wt%, the auxiliary metal loading is 0.5-5%, the preparation process is simple, the catalyst cost is low, and it is a CO catalytic oxidation catalyst with high sulfur resistance. When the auxiliary metal M is selected as Ni or Y, the sulfur resistance catalytic stability of the corresponding catalyst is better. The catalyst prepared by the present invention is particularly suitable for the catalytic combustion of steel tail gas CO, and has high sulfur resistance, and can still maintain high activity to CO gas in a 300ppm SO2 environment, and has great industrial application potential and value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The comparison results of CO conversion rate of catalysts of Examples 1-7 of the present invention when catalytic combustion reaches stability at different reaction temperatures in the presence of 300 ppm SO2 gas.

[0022] Figure 2 The results are a comparison of the CO conversion rates of the catalysts of Example 1 and Comparative Examples 1-2 when the catalytic combustion reaches stability at different reaction temperatures in the presence of 300 ppm SO2 gas.

[0023] Figure 3 The catalyst stability curve of Example 1 catalyst applied to the continuous reaction of catalytic combustion of CO;

[0024] Figure 4 The catalyst stability curve of Example 2 when the catalyst is applied to the continuous reaction of catalytic combustion of CO;

[0025] Figure 5 This is the catalyst stability curve of Example 5 when the catalyst is applied to the continuous reaction of catalytic combustion of CO.

[0026] Figure 6 The catalyst stability curve of Example 3 when the catalyst is applied to the continuous reaction of catalytic combustion of CO.

[0027] Figure 7 The catalyst stability curve of Example 4 when the catalyst is applied to the continuous reaction of catalytic combustion of CO.

[0028] Figure 8 Catalyst stability curve of Example 6 when the catalyst is applied to the continuous reaction of catalytic combustion of CO.

[0029] Fig. 9 Catalyst stability curve of Example 7 when the catalyst is applied to the continuous reaction of catalytic combustion of CO. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0031] Example 1

[0032] Step 1: Dissolve 6.4984g La(NO3)3·6H2O and 54.4576g Al(NO3)3·9H2O in 200ml deionized water as solution A, and dissolve 5.4458g titanium isopropoxide in 6.8072g ethanol as solution B. Add solution B and 1mol / L ammonia solution to solution A while stirring vigorously, and adjust the pH value to 9.0. Stir the mixture for 3h, age it at room temperature for 12h, filter it, wash it with deionized water several times until the filtrate is neutral, dry it at 110℃ for 12h, and calcine it at 400℃ in air atmosphere for 4h to obtain Ti 10 La 10 Al 80 O x A composite oxide support, wherein the molar ratio of Ti / La / Al is 10:10:80.

[0033] Step 2: Dissolve 4 mL of chloropalladic acid solution (Pd concentration in the solution is 2.5 g / L) in 20 mL of deionized water and add the TiLaAlO x 1.0 g of the carrier powder was dispersed in a chloropalladic acid solution, and the resulting mixture was stirred in a 75°C water bath for 1 h and then filtered, dried at 110°C for 1 h, and calcined at 400°C for 4 h to obtain 1 wt% Pd / TiLaAlO x catalyst.

[0034] Comparative Example 1:

[0035] 1wt%Pd / TiAlO x The preparation steps of the catalyst were repeated in Example 1, except that La(NO3)3·6H2O was not added in the first step, and the other conditions remained unchanged, and finally 1wt% Pd / TiAlO x catalyst.

[0036] Comparative Example 2:

[0037] 1wt%Pd / LaAlO x The preparation steps of the catalyst were repeated in Example 1, except that titanium isopropoxide was not added in the first step, and the other conditions remained unchanged, and finally 1wt% Pd / LaAlO x catalyst.

[0038] Example 2

[0039] Step 1: Dissolve 6.4984g La(NO3)3·6H2O and 54.4576g Al(NO3)3·9H2O in 200ml deionized water as solution A, and dissolve 5.4458g titanium isopropoxide in 6.8072g ethanol as solution B. Add solution B and 1mol / L ammonia solution to solution A while stirring vigorously, and adjust the pH value to 9.0. Stir the mixture for 3h, age it at room temperature for 12h, filter it, wash it with deionized water several times until the filtrate is neutral, dry it at 110℃ for 12h, and calcine it at 400℃ in air atmosphere for 4h to obtain Ti 10 La 10 Al 80 O x A composite oxide support, wherein the molar ratio of Ti / La / Al is 10:10:80.

[0040] Step 2: Weigh 0.1189 g Ni(NO3)2·6H2O and dissolve it in deionized water. Add 1.2 g TiLaAlO x The powder was stirred in a 60°C water bath for 30 min, and the obtained mixture was subjected to vacuum rotary evaporation to remove excess water to obtain a solid powder, which was dried overnight and calcined at 500°C for 4 h to obtain the modified carrier TiLaAlO x -Ni, Ni loading 2wt%.

[0041] Step 3: Dissolve 4 mL of chloropalladic acid solution (Pd concentration in the solution is 2.5 g / L) in 20 mL of deionized water, disperse 1.0 g of the modified carrier powder obtained in step 2 in the chloropalladic acid solution, stir the resulting mixture in a 75°C water bath for 1 h, filter, dry at 110°C for 1 h, and calcine at 400°C for 4 h to obtain 1 wt% Pd / TiLaAlO x -Ni catalyst.

[0042] Example 3

[0043] The same operation as in Example 2 was performed, except that in the second step, 0.1189 g Ni(NO3)2·6H2O was replaced by 0.1731 g Fe(NO3)3·9H2O, and the other conditions remained unchanged to obtain 1 wt% Pd / TiLaAlO x -Fe catalyst, Fe loading 2wt%.

[0044] Example 4

[0045] The same operation as in Example 2 was performed except that 0.1189 g Ni(NO3)2·6H2O was replaced by 0.1185 g Co(NO3)2·6H2O in the second step, and the other conditions remained unchanged to obtain 1 wt% Pd / TiLaAlO x-Co catalyst.

[0046] Example 5

[0047] The same operation as in Example 2 was performed except that 0.1189 g Ni(NO3)2·6H2O was replaced by 0.1033 g Y(NO3)3·6H2O in the second step, and the other conditions remained unchanged to obtain 1 wt% Pd / TiLaAlO x -Y catalyst.

[0048] Example 6

[0049] The same operation as in Example 2, except that in the second step, 0.1189 g Ni(NO3)2·6H2O was replaced by 0.1388 g C 10 H5B 20 , the other conditions remain unchanged, and 1wt% Pd / TiLaAlO x -Nb catalyst.

[0050] Example 7

[0051] The same operation as in Example 2 was performed except that 0.1189 g Ni(NO3)2·6H2O was replaced by 0.0906 g Cu(NO3)2·3H2O in the second step, and the other conditions remained unchanged to obtain 1 wt% Pd / TiLaAlO x -Cu catalyst.

[0052] Application Example 1:

[0053] The catalysts prepared in Examples 1-7 were respectively applied to the catalytic combustion reaction of CO. The reaction conditions were as follows: 0.1 g of the catalyst was loaded into a tubular reactor and heated to the reaction temperature of the catalytic combustion. The total flow rate of the gas feed was 100 ml / min, the reaction space velocity was 60,000 ml / g·h, the volume fraction of CO in the gas feed was 1%, the SO2 concentration was 300 ppm, and the dilution gas for the gas feed was air.

[0054] According to the above test conditions, the comparison results of CO conversion rate when catalytic combustion reaches stability at different reaction temperatures are shown in Figure 1 .from Figure 1 It can be seen that the catalysts of Examples 2, 3 and 5 have higher catalytic activity in the presence of SO2.

[0055] According to the above test conditions, the 1wt% Pd / TiLaAlO x Catalyst, 1wt% Pd / TiAlO of Comparative Example 1 x Catalyst and 1wt% Pd / LaAlO of Comparative Example 2 xThe comparison results of CO conversion rate when the catalytic combustion reaches stability are shown in Figure 2 .

[0056] Application Example 2:

[0057] The catalysts prepared in Examples 1, 2, and 5 were respectively applied to the reaction of catalytic combustion of CO, and the reaction conditions were: 0.1 g of the catalyst was loaded into a tubular reactor, heated to a reaction temperature of 220°C for catalytic combustion, the total flow rate of the gas raw material was 100 ml / min, the reaction space velocity was 60000 ml / g·h, the volume fraction of CO in the gas raw material was 1%, and the diluent gas of the gas raw material was air. When conducting a continuous catalytic combustion experiment, SO2 was not introduced into the gas raw material during the reaction time of 0-1h, SO2 with a final concentration of 300 ppm was introduced into the gas raw material during the reaction time of 1-4h, and SO2 was not introduced into the gas raw material again during the reaction time of 4-7h.

[0058] According to the above test conditions, the catalysts of Examples 1, 2, 5, 3, 4, 6, and 7 were respectively applied to the continuous reaction of catalytic combustion of CO, and the catalyst stability curves were shown in FIG. Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 and Fig. 9 That is to say, Figure 3-9 The 300ppm SO2 between the two dotted lines means that 300ppm SO2 gas was introduced during this time period, and the gas composition was CO+SO2+air. The other time periods were all CO+air.

[0059] Figure 2 These are the performance test results of the catalyst without adding additives. The catalyst has poor resistance to SO2 and begins to deactivate as soon as SO2 is introduced. The conversion rate to CO drops sharply, and the activity is difficult to recover after the introduction of SO2 is stopped, indicating that the catalyst is poisoned and has caused irreversible deactivation. Figure 3 , 4 The sulfur resistance of the catalyst was improved after adding the modified additives Ni and Y. After the introduction of SO2, the catalyst still maintained a certain activity, maintaining a conversion rate of more than 75% for CO, and the activity returned to 100% after the introduction was stopped.

[0060] Figure 6-Figure 9 It can be seen that the addition of other modification additives does not significantly improve the sulfur resistance of the catalyst.

[0061] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A low-temperature CO catalytic oxidation catalyst with high sulfur resistance, characterized in that The catalyst carrier is TiLaAlO x The composite metal oxide is loaded with active ingredients and auxiliary metal M on the carrier, the active ingredient is precious metal Pd, the auxiliary metal M is one or more of Co, Cr, Cu, Sn, Mo, W, Fe, Y, Ni, and Nb, the Pd loading is 0.1-4%, and the auxiliary metal M loading is 0.5-5%; the TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is 5-15:5-15:

80.

2. A low-temperature CO catalytic oxidation catalyst with high sulfur resistance as claimed in claim 1, characterized in that The Pd loading is 0.5-2%, the auxiliary metal M loading is 1-2%, and the TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is 8-12:8-12:

80.

3. A low-temperature CO catalytic oxidation catalyst with high sulfur resistance as claimed in claim 1, characterized in that The auxiliary metal M is one or two of Ni and Y.

4. A method for preparing a low-temperature CO catalytic oxidation catalyst with high sulfur resistance as claimed in any one of claims 1 to 3, characterized in that The following steps are involved: S1: According to TiLaAlO x The molar ratio of Ti, La and Al in the composite metal oxide is determined, La(NO3)3·6H2O and Al(NO3)3·9H2O are dissolved in water, a titanium isopropoxide solution diluted with an ethanol solvent is added dropwise thereto, a base is added to adjust the pH to 8.0-10.0, and the mixture is stirred for 0.5-4 h; then, it is aged at room temperature for 10-15 h, filtered, washed with deionized water and anhydrous ethanol for several times until the filtrate is neutral, dried, and calcined at 300-600°C in an air atmosphere for 2-5 h to obtain TiLaAlO x Composite oxide powder; S2: Dissolve the nitrate of metal M in deionized water and add TiLaAlO x The composite oxide powder is stirred in a water bath at 50-70°C for 20-60 min, the resulting mixture is subjected to vacuum rotary evaporation to remove excess water to obtain a solid powder, which is dried overnight and calcined at 300-600°C for 2-5 h to obtain a modified carrier TiLaAlOx-M; S3: The precious metal is loaded by the equal volume impregnation method. The carrier powder obtained in step S2 is impregnated in the Pd precursor aqueous solution. The obtained mixture is stirred in a water bath at 65-85°C for 1-3 h to allow the precious metal Pd to be fully adsorbed on the carrier surface. The mixture is then filtered and dried. The mixture is calcined at 300-600°C in an air atmosphere for 2-5 h. The preparation is completed.

5. The method for preparing a low-temperature CO catalytic oxidation catalyst with high sulfur resistance as claimed in claim 4, characterized in that In step S1, S2 or S3, the calcination temperature is 380-420°C.

6. The method for preparing a low-temperature CO catalytic oxidation catalyst with high sulfur resistance as claimed in claim 4, characterized in that In step S3, the temperature of the stirring reduction reaction is 65-85° C., and the reaction time is 0.5-2 h.

7. Application of a low-temperature CO catalytic oxidation catalyst with high sulfur resistance in catalytic combustion of CO as claimed in claim 1, characterized in that The catalyst is loaded into a tubular reactor and heated to the reaction temperature of catalytic combustion. The CO gas is diluted with air as a diluent to form a gaseous raw material, which is then introduced into the tubular reactor for catalytic combustion reaction.

8. The use according to claim 7, characterized in that The CO gas concentration in the gas raw material is 1000ppm to 20000ppm, preferably 5000-10000ppm, the SO2 gas concentration in the gas raw material is 0-600ppm, and the reaction space velocity is 20000-80000mL·g -1 ·h -1 .

9. The use according to claim 7, characterized in that The reaction temperature of the catalytic combustion is 160-250°C, preferably 200-220°C.

10. The use according to claim 8, characterized in that The SO2 gas concentration in the gas raw material is below 300 ppm.

Citation Information

Patent Citations

  • Supported catalyst for oxygen-lacking combustion of low concentration combustible components in liquid-nitrogen wash exhaust gases, preparation method and application thereof

    CN106268740A

  • Sulfur-tolerant volatile organic compound combustion catalyst and preparation method and application thereof

    CN112871164A

  • Ruthenium-based noble metal combustion catalyst for low-carbon oxygen-containing organic waste gas as well as preparation method and application of ruthenium-based noble metal combustion catalyst

    CN115106101A

  • High-thermal-stability platinum-based methanol combustion catalyst as well as preparation method and application thereof

    CN117138777A

  • High surface area fibrous catalyst support,catalysts and processes

    GB1425631A